ISLAMIC SOCIAL REPORTING (ISR) PADA PERBANKAN SYARIAH DI INDONESIA - lulu amalia nusron; rani eka diansari (Universitas Lancang Kuning, 2021)
This study aims to determine Profitability, Liquidity, Company Size, and Leverage on Islamic Social Reporting (ISR) in Islamic Banking in Indonesia. The research period is 2016-2019. This study uses a quantitative approach. The population is all sharia banking in Indonesia registered with the OJK in 2016-2019. The sample was determined by purposive sampling technique, so that there were 32 financial reports from 8 BUS. Analysis makes use of multiple linear regression. The results concluded that (1) Profitability has no effect on Islamic Social Reporting. (2) Liquidity has no effect on Islamic Social Reporting. (3) Company size has no effect on Islamic Social Reporting. (4) Leverage affects Islamic Social Reporting. (5) Company age has no effect on Islamic Social Reporting. (6) Islamic Governance Score has no effect on Islamic Social Reporting. Keywords: Profitability, Liquidity, Company Size, Leverage, Company Age, Islamic Governance Score, Islamic Social Reporting (ISR) Disclosure.